CRYSTAL STRUCTURE OF TRIPHENYLTIN (IV) FORMATE POLYMER, (HCO2SnPh3)n - MODOU SARR; MOUHAMADOU BIRAME DIOP; AMINATA DIASSE-SARR; AI WANG; ULLRICH ENGLERT (Journal of Engineering Studies and Research)
The title polymer [HCO2Sn(C6H5)3]n was isolated by serendipitous from reaction in ethanol 96 % between bis-(monocyclohexyl ammonium) 2-carboxyethyl hydrogen phosphonate, {(CyNH3)2[CO2CH2CH2PO2(OH)]} and triphenyltin chloride, SnPh3Cl. The polymer crystallizes in the monoclinic space group P21/n with Z = 4, a = 14.7091 (18) Å, b = 15.4133 (19) Å, c = 14.7639 (18) Å, β = 94.242 (2)° and V = 3338.0 (7) Å3. The structure consists of an infinite chain propagating along the crystallographic a-axis direction with bidentate formate anions. The O2SnC3 core is organized into a trans-trigonal bipyramidal like-arrangement.